2016
DOI: 10.1002/smll.201603135
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Virus Capture and Release by a Microfluidic Device Integrated with Porous Silicon Nanowire Forest

Abstract: Viral diseases are perpetual threats to human and animal health. Detection and characterization of viral pathogens require accurate, sensitive and rapid diagnostic assays. For field and clinical samples, the sample preparation procedures limit the ultimate performance and utility of the overall virus diagnostic protocols. Here, we presented the development of a microfluidic device embedded with porous silicon nanowire (pSiNW) forest for label-free size-based point-of-care virus capture in a continuous curved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Diagnosis and treatment of viral infections require isolation of sub-micrometer viral particles and proteins from bodily fluids containing a large background of endogenous human cells. Direct manipulation of viral particles (20–400 nm) is challenging in inertial microfluidic (IM) because it is difficult to achieve sufficient shear gradient forces to influence nanoscale viruses [ 185 , 186 ]. Consequently, IM technologies focus on the indirect isolation of viruses [ 185 , 186 ] and clinically relevant antibodies [ 187 ] from blood samples by inertially focusing large blood cells for removal.…”
Section: Exogenous Targetsmentioning
confidence: 99%
“…Diagnosis and treatment of viral infections require isolation of sub-micrometer viral particles and proteins from bodily fluids containing a large background of endogenous human cells. Direct manipulation of viral particles (20–400 nm) is challenging in inertial microfluidic (IM) because it is difficult to achieve sufficient shear gradient forces to influence nanoscale viruses [ 185 , 186 ]. Consequently, IM technologies focus on the indirect isolation of viruses [ 185 , 186 ] and clinically relevant antibodies [ 187 ] from blood samples by inertially focusing large blood cells for removal.…”
Section: Exogenous Targetsmentioning
confidence: 99%
“…Xia et al developed a microfluidic device embedded with porous silicon nanowire (pSiNW) forest for label‐free size‐based point‐of‐care virus capture in a continuous curved flow design. They worked on Influenza virus (H5N1) and demonstrated that this method could have high potentials for virus discovery, isolation, and culture 84 …”
Section: Microfluidic Devicesmentioning
confidence: 99%
“…Cross-flow microfiltration has a wide range of applications, such as separation on nano- 162 and microscales, 163 enrichment, 244 and isolation of extracellular vesicles 164 and CTCs 161 from complex biosamples. Yoon et al 161 utilized weir filters to continuously separate CTCs from whole blood, achieving a separation efficiency of 97% [Fig.…”
Section: Sorting By Cross-flow Filtrationmentioning
confidence: 99%